2013
DOI: 10.2478/pjct-2013-0059
|View full text |Cite
|
Sign up to set email alerts
|

Removal of low molecular organic acids from aqueous solutions with reactive extraction

Abstract: This paper presents investigation on removal of low molecular organic acids (acetic, lactic, succinic and fumaric) from aqueous solutions with reactive extraction. The results specifi cally show that the extraction effi ciency of acids depends on the type of extractant, diluents of the organic phase and the initial pH of the aqueous phase. It is possible to separate succinic or fumaric from lactic and acetic acids with high selectivity with the use of TOA and Aliquat 336, respectively. Increasing the pH of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Reactive extraction method that depends on the chemical reaction between the solute and extractant molecules is an effective separation procedure because the desired component can be obtained with high purity, more selectivity, effective pH control of the fermentation process, low optional component arrangement, and low energy utilization. , Because of that, numerous investigations were carried out on the refinement of organic acids from aqueous phases utilizing the reactive extraction method. In the reported investigations, a few parameters were inspected, for example, starting acid amounts, the effect of the diluents, the effect of pH, and so on on the extraction system. These parameters are also the main parameters that have been investigated using other separation methods. …”
Section: Introductionmentioning
confidence: 99%
“…Reactive extraction method that depends on the chemical reaction between the solute and extractant molecules is an effective separation procedure because the desired component can be obtained with high purity, more selectivity, effective pH control of the fermentation process, low optional component arrangement, and low energy utilization. , Because of that, numerous investigations were carried out on the refinement of organic acids from aqueous phases utilizing the reactive extraction method. In the reported investigations, a few parameters were inspected, for example, starting acid amounts, the effect of the diluents, the effect of pH, and so on on the extraction system. These parameters are also the main parameters that have been investigated using other separation methods. …”
Section: Introductionmentioning
confidence: 99%
“…The reactive extraction technique that relies on the chemical interaction between the solute and extractant molecule is an encouraging separation method due to the product formation with high purity, high selectivity, and efficient pH control of the fermentation media, low secondary product formation, and low energy consumption since many investigations were performed for the purification of organic acids from aqueous solutions via reactive extraction. In these studies, several parameters have been observed such as initial acid concentration, the effect of the diluents, the effect of the pH, etc. on the extraction process.…”
Section: Introductionmentioning
confidence: 99%